Influence of Leadership Style on Employee Motivation and Performance in Nepalese Commercial Banks - Sah, Pratima (Nepalese Journal of Management, 2025)
This study examines the influence of leadership style on employee motivation and performance in Nepalese commercial banks. Employee motivation and employee performance are the dependent variables. The selected independent variables are transformational leadership style, transactional leadership style, laissez faire leadership style, autocratic leadership style, and democratic leadership style. The primary source of data is used to assess the opinions of respondents regarding transformational leadership style, transactional leadership style, laissez faire leadership style, autocratic leadership style, democratic leadership style, employee motivation, and employee performance. The study is based on primary data of 109 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of the influence of leadership style on employee motivation and employee performance. The study showed a positive impact of transformational leadership style on employee motivation and employee performance. It indicates that transactional leadership focuses more on extrinsic motivation that leads to increase in employee motivation and employee performance. Similarly, the study showed a positive impact of transactional leadership style on employee motivation and employee performance. It indicates that transactional leadership utilizes rewards and punishments to motivate the employees that leads to increase in employee motivation and employee performance. Likewise, the study also revealed a positive impact of laissez-faire leadership style on employee motivation and employee performance. It indicates that letting employees do as they choose leads to increase in employee motivation and employee performance. Further, the study observed a negative impact of autocratic leadership style on employee motivation and employee performance. It indicates that individual control over all decisions and little input from group members lead to decrease on employee motivation and employee performance. In addition, the study showed a positive impact of democratic leadership style on employee motivation and employee performance. It indicates that letting multiple employees participate in the decision-making process leads to increase in employee motivation and employee performance.